The Evaluation of Increase in Hemodialysis Frequency on C-Reactive Protein Levels and Nutritional Status - Ali Akbar Rashidi; Ali Reza Soleimani; Hassan Nikoueinejad; Shokooh Sarbolouki (Acta Medica Iranica, 2013)
Malnutrition and inflammation are the most important causes of cardiovascular disease in hemodialysis patients. This study was conducted to evaluate the effect of increase in hemodialysis frequency on C-reactive protein (CRP) level and nutritional markers in contrast to previous routine method. 18 hemodialysis patients with a mean age of 53±16 years were randomly selected in this before-and-after clinical trial. The patients under a standard hemodialysis of 3 times/4 h per week were converted to 4 times/4 h for a period of 6 weeks. The CRP, albumin, triglyceride, total cholesterol, LDL, HDL serum levels, anthropometric indices and 24-h diet recall intake was assessed before and after of the period. The data were analyzed using paired t-test, and P-value less than 0.05 was considered significant. All patients completed the study. Mean weight, body mass index and serum albumin increased while serum CRP level decreased significantly after the intervention (P<0.03). Triglyceride, total cholesterol, LDL, HDL, as well as energy, protein and fat intake had no significant change before and after the study. Increase in dialysis frequency decreased systemic inflammation and improved the nutritional state of hemodialysis patients. Therefore, it may decrease the risk of cardiovascular events in these patients.